Acoustics of suspended ceilings and speech privacy - Seddeq, H. S. (Canadian Acoustics, 2012)
Acoustics is an integral factor of indoor environmental quality, and it’s essential that suspended ceilings systems of modern office building provide adequate acoustical separation. This paper evaluates the acoustic performance for different suspended ceilings systems installed in rooms with dividing partitions as to their speech privacy characteristics. The relation between speech privacy index and ceiling attenuation class (CAC), articulation class (AC), and subjective speech privacy rating has also been presented in this paper.